2014
DOI: 10.1371/journal.pone.0105604
|View full text |Cite
|
Sign up to set email alerts
|

A Hypomagnetic Field Aggravates Bone Loss Induced by Hindlimb Unloading in Rat Femurs

Abstract: A hypomagnetic field is an extremely weak magnetic field—it is considerably weaker than the geomagnetic field. In deep-space exploration missions, such as those involving extended stays on the moon and interplanetary travel, astronauts will experience abnormal space environments involving hypomagnetic fields and microgravity. It is known that microgravity in space causes bone loss, which results in decreased bone mineral density. However, it is unclear whether hypomagnetic fields affect the skeletal system. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 69 publications
2
28
1
Order By: Relevance
“…By zero, we imply low in relationship to the geomagnetic field H geo of about 40000 nT. Many publications confirm the biological efficacy of such weak MFs [e.g., Choleris et al, ; Sarimov et al, ; Burger et al, ; Jia et al, ].…”
Section: Nonuniform Precession and Magnetoreceptionmentioning
confidence: 86%
See 1 more Smart Citation
“…By zero, we imply low in relationship to the geomagnetic field H geo of about 40000 nT. Many publications confirm the biological efficacy of such weak MFs [e.g., Choleris et al, ; Sarimov et al, ; Burger et al, ; Jia et al, ].…”
Section: Nonuniform Precession and Magnetoreceptionmentioning
confidence: 86%
“…By zero, we imply low in relationship to the geomagnetic field H geo of about 40000 nT. Many publications confirm the biological efficacy of such weak MFs [e.g., Choleris et al, 2002;Sarimov et al, 2008;Burger et al, 2010;Jia et al, 2014]. Interestingly, h ¼ H ¼ 0 is not the only magnetic mode for significant changes in the natural precession.…”
Section: Stopping the Magnetic Moment Precessionmentioning
confidence: 87%
“…We raise a hypothesis that 16 T SMF had inhibited effects on osteoclast activity, while its formation and differentiation could be enhanced by intensities of 500 nT and 0.2 T. In order to test our hypothesis, we investigated the regulatory role of SMFs on osteoclastogenesis and the ability of the bone resorption of osteoclast precursor RAW264.7 cells under such SMFs as HyMF, GMF, MMF to HiMF. The present study utilized HyMF of about 500 nT (created by a magnetic shielding room), MMF of 0.2-0.4 T (surrounding a superconducting magnet) and HiMF of 16 T (generated by a superconducting magnet) based on our previous studies (Jia et al, 2014;Wang et al, 2009;Qian et al, 2009Qian et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that HyMF has a negative impact on many aspects of life activities, including the structure and function of the central nervous system, circadian rhythm, and bone in the body . We have shown that HyMF can accelerate HLU‐induced bone loss in rats and mice . In this study, we explored the effects of HyMF on bone of HLU mice in reloading.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, we found that HyMF can inhibit osteoblast differentiation and mineralization, and promote osteoclast formation and bone resorption . In vivo, HyMF aggravated bone loss induced by hindlimb unloading (HLU) in rats and mice . Therefore, as an non‐negligible risk factor in space, HyMF participates in spatial bone loss.…”
Section: Introductionmentioning
confidence: 92%